2005
DOI: 10.1007/s00167-005-0641-x
|View full text |Cite
|
Sign up to set email alerts
|

A long-term follow-up study after medial patellofemoral ligament reconstruction using the transferred semitendinosus tendon for patellar dislocation

Abstract: The management of patellar dislocation syndrome has traditionally been difficult. There are no golden standard methods for patellar dislocations probably due to the many etiologies. However, it is known that medial patellofemoral ligament (MPFL) is damaged when the patella is dislocated. The purpose of this study is to examine whether our method of MPFL reconstruction is useful for the treatment of dislocated patellae and unstable patellae. Forty-six knees (43 patients) of 68 knees (65 patients) that were oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
189
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(205 citation statements)
references
References 15 publications
7
189
1
8
Order By: Relevance
“…In a recent meta-analysis, a total of 1,065 MPFL reconstructions were identified in 31 studies, and it was found that autograft reconstructions were associated with greater postoperative improvements in Kujala scores when compared to allograft, and that double-limbed reconstructions were associated with both improved postoperative Kujala scores and lower failure rate [58]. Overall, in the absence of significant malalignment, MPFL reconstructions appear to provide long-term functional improvement with improved Kujala scores, low rate of redislocation, and decreases in apprehension and patellofemoral pain [59,60,61,62,63,64]. However, the current literature on MPFL outcomes has substantial methodological limitations with small sample sizes and limited follow-ups [65].…”
Section: Surgical Managementmentioning
confidence: 99%
“…In a recent meta-analysis, a total of 1,065 MPFL reconstructions were identified in 31 studies, and it was found that autograft reconstructions were associated with greater postoperative improvements in Kujala scores when compared to allograft, and that double-limbed reconstructions were associated with both improved postoperative Kujala scores and lower failure rate [58]. Overall, in the absence of significant malalignment, MPFL reconstructions appear to provide long-term functional improvement with improved Kujala scores, low rate of redislocation, and decreases in apprehension and patellofemoral pain [59,60,61,62,63,64]. However, the current literature on MPFL outcomes has substantial methodological limitations with small sample sizes and limited follow-ups [65].…”
Section: Surgical Managementmentioning
confidence: 99%
“…A systematic review of the literature demonstrates no one technique to be superior. Despite this reconstruction of the MPFL has demonstrated excellent clinical results across a number of series, with low levels of re-dislocations [64,[78][79][80][81]. MPFL reconstruction offers an appropriate treatment modality in a chronic situation.…”
Section: Mpfl Reconstructionmentioning
confidence: 99%
“…There is still much controversy associated with aetiological factors, pathological changes and treatment, especially in the choice of surgical method [1]. There are many traditional treatments, including proximal and distal realignment and soft tissue procedures, which lead to a high rate of recurrence and an increased incidence of osteoarthritis in the patellofemoral joint postoperatively at long-term follow-up [2]. Trochlear dysplasia is one of the most consistent anatomic factors that can lead to habitual patellar dislocations.…”
Section: Introductionmentioning
confidence: 99%